Features of development and harmfulness of the berry bug in grain crops in the north-west of Russia - A. M. Shpanev; A. V. Kapustkina (Зерновое хозяйство России, 2023)
In 2022, a mass propagation of the berry bug occurred in the North-West of Russia, which had no analogues over the past decade. This made it possible to study in detail some issues of its biology and harmfulness on grain crops. The purpose of the current study was to determine food specialization, long-term population dynamics, seasonal development, and harmfulness of the berry bug in grain crops in the North-West of the Russian Federation. For this purpose, there was carried out regular mowing with an entomological net, timed to coincide with the phonological development of cultivated plants, the total number of which was 2544, of which 1380 were on grain crops. The estimation of the harmfulness of the berry bug was carried out on winter triticale by simply comparing the mass of damaged and undamaged caryopses. According to the study results, there has been revealed that grain crops were populated to a greater extent than agrocenoses of other crops. Among grain crops, winter triticale turned out to be the most populated crop, and winter rye was the least populated. The maximum number of berry bug occurred during the period of maturation of grain crops, when larvae of different ages feeding on caryopses were predominantly found in the crops. The study of topical confinement showed that the largest number of bugs’ pricks were located in the middle part of the caryopsis and mainly on the sides (75.0 %). Analysis of the harvested crop of winter triticale revealed that damage to the grain caused by berry bug was 6.4 %, 5.0 % of which 1–2 points, 1.4 % of which 3 points. Depending on the damage scale, the decrease in 1 caryopses weight was from 6.6 to 18.2 mg (13.2–36.5 %), the yield was 0.061 ton/ha (1.2 %). Thus, despite the high density of winter triticale crops with berry bug in the conditions of 2022, the proportion of damaged caryopses and their damage degree, as well as the total yield loss, turned out to be low, which means that the use of insecticides was inappropriate.